KONSEPTUALISASI PENGELOLAAN PERIKANAN LAUT SKALA KECIL BERBASIS LOKASI PKN (Peningkatan Kehidupan Nelayan) (Study Kasus: Wilayah Kecamatan PKN Kabupaten Nagan Raya) - Farah Diana; Muhammad Rizal (Universitas Teuku Umar, 2016)
Capture fisheries are very important economic activity and have contributed greatly to the total fishery production in general in the District Naganraya. Fishery system that occurs dominated by small-scale fisheries. Fishermen in Naganraya district has a high dependence on fisheries resources as the main source of livelihood and almost all coastal areas based fisheries activities. Small-scale fisheries businesses have an impact on the fishing fleet and fishing locations (fishing ground) resulting in range of fishing operations is limited. The purpose of this research is 1). Analyzing small-scale capture fisheries system in locations PKN Naganraya district, 2). Formulate an alternative strategy in the management of small-scale fishing locations PKN Naganraya district. Data to be collected in this study consisted of primary and secondary data. Primary data was collected intensively using semi-structured interviews (semi-structured interview) to small-scale fishermen, observation and documentation in selected locations. The results showed that the dominant type of fishing gear is trawl catches beach and species that dominate the catch is Sardinella lemuru and Selar spp. Fish marketing patterns in locations peningkapan fishing activities (PKN) is not through the auction only through traders / large and are twelve strategic through internal and external environmental factors were dominant influence on the pattern of the conceptualization of small-scale fishery management in PKN location Nagan Raya.